The Image and Data Archive at the Laboratory of Neuro Imaging - Crawford, Karen L. (Neuroimage, 2015)
The LONI Image and Data Archive (IDA)() is a repository for sharing and long-term preservation of neuroimaging and biomedical research data. Originally designed to archive strictly medical image files, the IDA has evolved over the last ten years and now encompasses the storage and dissemination of neuroimaging, clinical, biospecimen, and genetic data. In this article, we report upon the genesis of the IDA and how it currently securely manages data and protects data ownership.